2022
DOI: 10.3389/fnins.2022.1011475
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of MUSE 2 and Tobii Pro Nano at capturing mobile application users' real-time cognitive workload changes

Abstract: IntroductionDespite the importance of cognitive workload in examining the usability of smartphone applications and the popularity of smartphone usage globally, cognitive workload as one attribute of usability tends to be overlooked in Human-Computer Interaction (HCI) studies. Moreover, limited studies that have examined the cognitive workload aspect often measured some summative workloads using subjective measures (e.g., questionnaires). A significant limitation of subjective measures is that they can only ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…For example, the reliability of devices such as Empatica E4 and Muse, which were used in the reviewed studies (Antoniou et al, 2020;Brunzini et al, 2022), is questionable (Borrego et al, 2019;Karwowski et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the reliability of devices such as Empatica E4 and Muse, which were used in the reviewed studies (Antoniou et al, 2020;Brunzini et al, 2022), is questionable (Borrego et al, 2019;Karwowski et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One of them is a choice of measuring device and analysis algorithm. For example, the reliability of devices such as Empatica E4 and Muse, which were used in the reviewed studies (Antoniou et al, 2020; Brunzini et al, 2022), is questionable (Borrego et al, 2019; Karwowski et al, 2022). The choice of EEG channels also presents uncertain reliability.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bailey & Iqbal showcased the potential of eye tracking in monitoring CW fluctuations during interactive tasks through pupil dilation [67]. Similarly, Zhang & Cui validated the reliability of the Tobii Pro Nano eye tracker in detecting CW changes in real-time during N-back tasks [68]. Wu et al, further, demonstrated the predictive capability of eye-tracking metrics in estimating CW levels with an accuracy of 84.7% during robotic surgical training [69].…”
Section: Physiological Signals Acquired Through Wearable Sensors For Hmimentioning
confidence: 93%
“…Notably, DreamMachine stands out for its affordability, with a manufacturing cost below 150 euros (for the time needed to design and produce the board). In the mobile EEG market, OpenBCI and Muse 2 have emerged as prominent choices, offering cost-effective solutions without compromising performance [9][10][11]. While other mobile EEG devices like MindWave Mobile2 [12], Emotiv EPOC+ [13], and the unicorn hybrid black [14] are recognized for their advanced features and higher price points, Muse 2 and OpenBCI provide more accessible alternatives [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…While other mobile EEG devices like MindWave Mobile2 [12], Emotiv EPOC+ [13], and the unicorn hybrid black [14] are recognized for their advanced features and higher price points, Muse 2 and OpenBCI provide more accessible alternatives [15,16]. However, it is important to acknowledge the limitations of these devices, including a limited number of channels-16 channels for the Cyton+Daisy board from OpenBCI [17] and 4 channels for the Muse 2 [11]. A higher cost of $1999.00 USD for the OpenBCI system and 249 USD for the Muse 2, along with potential challenges in terms of accessibility, which may pose constraints for certain student and research budgets, are noted.…”
Section: Introductionmentioning
confidence: 99%